Solar wind sputtering of lunar analogue material. Issue 20 (January 2020) - Szabo, P S; Biber, H; Weichselbaum, D; Brenner, M; Stadlmayr, R; Mayer, D; Mutzke, A; Nenning, A; Doppler, M; Sauer, M; Jäggi, N; Galli, A; et al.
Synopsis: Sputtering by solar wind ions is investigated on thin films of the mineral wollastonite (CaSiO3 ) as an analogue material for the lunar surface. Sputtering yields are measured with a Quartz Crystal Microbalance (QCM) using H and He ions as well as multiply charged Ar ions at different incidence angles. The results of these irradiations show that kinetic sputtering can be very well reproduced using SDTrimSP, while potential sputtering significantly increases the expected erosion of airless bodies in the solar system.